Strengthening and Sustaining Social Supports for Rural Elders - Kristie J. Clark; Beverly D. Leipert (Online Journal of Rural Nursing and Health Care, 2012)
Rural elders face unique challenges in maintaining and strengthening their social supports. The purpose of this paper is to examine factors that influence social supports for rural elders as well as to identify implications for nursing practice and research. An extensive review of the literature revealed that rural elder social support is affected by factors related to outmigration of youth, geographical distance, transportation, decreased income, as well as rural culture, values, and norms. The literature also reviewed strategies that can facilitate social support in rural areas, including multiple use of one site, use of technology, mobile and outreach services, community development initiatives, and transportation projects. Rural nurses have a professional responsibility to share their knowledge of ways to sustain social supports for rural seniors, and to advocate for better funding and programs for this population. However, in order to prepare nurses to effectively advocate on behalf of rural seniors, education for nurses that encompasses the context of rural health is needed.